2019
DOI: 10.1105/tpc.18.00757
|View full text |Cite
|
Sign up to set email alerts
|

Danger-Associated Peptides Interact with PIN-Dependent Local Auxin Distribution to Inhibit Root Growth in Arabidopsis

Abstract: Plant elicitor peptides (Peps) are damage/danger-associated molecular patterns that are perceived by the receptor-like kinases, PEPR1 and PEPR2, to enhance innate immunity and to inhibit root growth in Arabidopsis (Arabidopsis thaliana). Here, we show that Arabidopsis Pep1 inhibits root growth in a PEPR2-dependent manner, which is accompanied by swelling epidermal and cortex cells and root hair formation in the transition zone (TZ). These Pep1-induced changes were mimicked by exogenous auxin application and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 71 publications
(140 reference statements)
10
54
0
2
Order By: Relevance
“…To investigate whether Pep1 interacts with pH signaling to regulate the root growth, we examined the effects of 100 nM Pep1 in the plant growth medium with different pH (4.5 to 8.0) on the growth of wild-type (WT) seedlings. Pep1 treatment induced a significant root growth inhibition under normal pH (5.8) condition ( Figure 1A,B), in agreement with previous results [15]. Interestingly, we found that Pep1's effect on root growth was dependent on the pH changes, as decreasing of medium pH (4.5-5.8) further aggravated the Pep1-induced root growth inhibition, however, increasing of medium pH into faintly acid (pH 6.4), neutral (pH 7.2), or alkali (pH 8.0) condition significantly alleviated the Pep1 effect on root growth ( Figure 1A,B).…”
Section: Pep1 Inhibits the Root Growth Dependent On Ph Changessupporting
confidence: 93%
See 4 more Smart Citations
“…To investigate whether Pep1 interacts with pH signaling to regulate the root growth, we examined the effects of 100 nM Pep1 in the plant growth medium with different pH (4.5 to 8.0) on the growth of wild-type (WT) seedlings. Pep1 treatment induced a significant root growth inhibition under normal pH (5.8) condition ( Figure 1A,B), in agreement with previous results [15]. Interestingly, we found that Pep1's effect on root growth was dependent on the pH changes, as decreasing of medium pH (4.5-5.8) further aggravated the Pep1-induced root growth inhibition, however, increasing of medium pH into faintly acid (pH 6.4), neutral (pH 7.2), or alkali (pH 8.0) condition significantly alleviated the Pep1 effect on root growth ( Figure 1A,B).…”
Section: Pep1 Inhibits the Root Growth Dependent On Ph Changessupporting
confidence: 93%
“…In the process of revealing the role of Pep-PEPR in plants, we found that binding of Pep1 to PEPR2 induced a strong root growth inhibition, accompanied by swelling epidermal and cortical cells in root transition zone (TZ) [15]. In this study, we revealed that Pep1 treatment inhibited the root growth by activating the PM H + -ATPase to extrude the protons into apoplast, which induced an overly acidic environment in apoplast to inhibit root growth.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations